The First Amendment and the Off-Duty Conduct of Public Employees: Tradeoffs Among Civil Liberties, Agency Mission, and Public Trust. (4th May 2018) - Foote, Paul Douglas; Clinger, James
Abstract : This article examines the dilemmas that public managers face in dealing with controversial off-duty speech and/or organizational affiliations by their employees. While public employees have First Amendment and, often, civil service protections against retaliation from superiors for their off-the-clock conduct, agency executives and managers have disciplined or dismissed employees because of expression and/or group affiliations deemed incompatible with the mission of their agencies. This article examines the pertinent case law, as well as the ethical conflicts over allowing diverse viewpoints in the workforce while at the same time managing organizations that implement policies that have particular purposes that are incompatible with some viewpoints. The possibility that the disciplining of employees, or the failure to discipline them, may affect public trust in government is explored.